1972
DOI: 10.1128/jb.111.2.542-546.1972
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Intracellular Adenosine Triphosphate Pool of Saccharomyces cerevisiae to Growth Inhibition Induced by Excess l -Methionine

Abstract: Yeast cells accumulate S-adenosyl-L-methionine (S-AM) when cultivated in the presence of L-methionine. Cell growth is inhibited by the addition of high concentrations of L-methionine. A number of investigators have attributed this to the depletion of adenosine triphosphate (ATP) as a consequence of the utilization of that mucleotide for S-AM formation. The cellular ATP pool of Saccharomyces cerevisiae was measured during growth inhibition caused by addition of excess L-methionine. Polyethylenimine thin-layer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
0

Year Published

1973
1973
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…The average determined value was 1,025 ,umol per 106 cells or 16.5 ,imol/g (dry weight) ( Table 2). This amount is comparable to the ATP level in mycelia of N. crassa of 12.8 ,imol/g (dry weight) (5,27) or a value of 200 to 1,000 ,umol per 106 cells determined for Saccharomyces cerevisiae (1). The constancy of the ATP pool size in Allomyces sp.…”
Section: Resultssupporting
confidence: 69%
“…The average determined value was 1,025 ,umol per 106 cells or 16.5 ,imol/g (dry weight) ( Table 2). This amount is comparable to the ATP level in mycelia of N. crassa of 12.8 ,imol/g (dry weight) (5,27) or a value of 200 to 1,000 ,umol per 106 cells determined for Saccharomyces cerevisiae (1). The constancy of the ATP pool size in Allomyces sp.…”
Section: Resultssupporting
confidence: 69%
“…The yeast accumulated high amount of lipid per cell dry weight, but the fair cell mass indicated that the initial AA concentrations used in the media were rather high, which might have created a stressful environment that impeded cellular performance. 42 Similar phenomena were observed using AA blends similar to FMAA, with a lipid productivity of 0.75 g L -1 day -1 . The cell mass, lipid, and lipid content were 7.5 g L -1 , 3.4 g L -1 , and 45.1%, respectively (Fig.…”
Section: Resultssupporting
confidence: 65%
“…1). We previously demonstrated successful lipid production with AA blends matching a similar AA compositional profile to sheep viscera AA (SVAA), 35 fish muscle AA (FMAA), 36 or meat industry by-product AA (MIAA), 37 as carbon substrates; 23,24 however, it was found that AA in high concentrations had adverse effects on cell viability and lipid production, which might have been due to the high osmotic stress, high intracellular AA level, 42 accumulation of ammonia or inhibitory metabolic intermediates, 43,44 or the very low C/N ratio of the media, as the C/N ratio of about 100 was found to be favorable for lipid production. 21,22 To improve the C/N ratio of the media and subsequently encourage microbial lipid production on AA, 20 g L -1 glycerol was supplied to the media containing the designated AA blends with similar AA compositions to SVAA, FMAA, and MIAA, respectively (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…121, 1975 mCi/mmol). After radioactivity had been incorporated for one to two generations, samples were collected and analyzed for nucleotide pools by thinlayer chromatography (2,6,7). Nucleoside triphosphates were localized by ultraviolet absorption and autoradiography.…”
mentioning
confidence: 99%